Gender issues in Islam: “Recovering the measure” and restoring the balance - El-Mesawi, Mohamed El-Tahir (International Institute of Islamic Thought - Bangladesh Office, 2017)
The debate on gender and gender-related issues has become an essential part of global discourses on women and male-female relationships, both at the level of individual writers and within official national and international bodies as well as NGOs. These discourses are characterized by extremes and polarities even on the part of Muslims who have participated in the debate. A much-needed fundamental ontological and ethical framework is lacking. Such a framework could set the discussion of women and gender issues on a balanced scale by taking all dimensions of human existence into account in a holistic manner as can be expressed by the doctrine of maqasid al-shari'ah. With this historical and intellectual background in view, the present article is an attempt at proposing such a framework as could be derived from the Qur'an, thus reflecting the Islamic worldview and its implications for our understanding of the human condition and the essential relationship between man and woman as the binary that represents the two facets of human nature and reality.